Divergent dynamics in systemic and tissue-specific metabolic and inflammatory responses during weight loss in subjects with obesity - Van de Velde, Frederique; Ouwens, D. Margriet; Batens, Arsène-Hélène; Van Nieuwenhove, Yves; Lapauw, Bruno (Cytokine (Philadelphia, Pa.), 2021)
•Weight loss improves systemic inflammation and insulin resistance in obese subjects.•Accompanied by corresponding molecular adaptations (e.g. IL-6) in metabolic tissues.•However, other molecular adaptations during weight loss are more divergent.•Molecular mechanisms contributing to better metabolic health appear tissue specific. Dysfunction of adipose and muscle tissue associates with obesity-related co-morbidities such as insulin resistance (IR) and inflammation. This study investigates changes in systemic and tissue-specific markers of IR and inflammation after gastric bypass surgery (GBS) in subjects with obesity. Prospective study, twenty subjects with obesity (50 ± 10 years, 14 men). Prior to, and six months and one year after GBS, subcutaneous abdominal adipose tissue (SAT), skeletal muscle and fasting serum samples were collected. Serum levels of C-reactive protein (CRP), glucose and insulin were determined using standard laboratory assays and serum IL-6, IL-10 and TNF-α levels were determined using ELISA. Tissue mRNA expression of inflammation and insulin/glucose metabolism markers were analyzed using qPCR. After GBS, HOMA-IR, CRP and IL-6 serum levels decreased. In SAT, expression of bone morphogenetic protein 4 (BMP4), IL-6, IL-10 and MCP1 decreased and GLUT4 increased (all p < 0.05). In muscle, expression of BMP4, GLUT4 and IL-6 decreased and of MCP1 and IRS-1 increased (all p < 0.05). Systemic improvements in inflammation and IR after GBS are only partially mirrored by corresponding changes in adipokine and myokine expression patterns. As changes in expression of other markers of inflammation and insulin/glucose metabolism appear less consistent and even divergent between tissues, the inflammatory and IR status at systemic level cannot be extrapolated to the situation in metabolically active tissues.